An Analysis of Domestic and International Research Trends of Assessment in Mathematics Education Using Topic Modeling - Taekwon Son; Sunghwan Hwang (Korea Society of Educational Studies in Mathematics, 2020)
Research into assessments in mathematics education has broadened from summative assessments focusing on students achievement to those focusing on students' cognition, curriculum, teaching and learning, teacher knowledge and quality, and affective domains. Considering these changes in assessment research, we examined the characteristics of domestic assessment research in mathematics education by comparing 237 articles published in KCI journals with 857 articles published in SSCI journals from 2000 to 2020 August. We used LDA topic modeling to examine research trends over time. The findings indicated that there were different keyword distributions by period between domestic and international mathematics education journals. There were nineteen research topics in both journals; five topics were similar while nine topics were different. In addition, the hot topics in international and domestic mathematics education journals were found to be curriculum assessment and student competency assessment, respectively. Based on these findings, we discussed practical implications for the development of assessment research in domestic mathematics education.